Potential of ATP5MG to Treat Metabolic Syndrome-Associated Cardiovascular Diseases - Liu, Lianyong; Zhou, Xinglu; Chen, Juan; Li, Xiangqi (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Metabolic Syndrome-associated Cardiovascular Disease (MetS-CVD) is a cluster of metabolism-immunity highly integrated diseases. Emerging evidence hints mitochondrial energy metabolism may be involved in MetS-CVD development. The physiopathological role of ATP5MG, a subunit of the F0ATPase complex, has not been fully elucidated. Methods: Here, we selected ATP5MG to identify the immunity-mediated pathway and mine drugs targeting this pathway for treating MetS-CVD. Using big data from public databases, we dissected co-expressed RNA (coRNA), competing endogenous RNA (ceRNA), and interacting RNA (interRNA) genes for ATP5MG. Results: It was identified that ATP5MG may form ceRNA with COX5A through hsa-miR-142-5p and interplay with NDUFB8, SOD1, and MDH2 through RNA-RNA interaction under the immune pathway. We dug out 251 chemicals that may target this network and identified some of them as clinical drugs. We proposed five medicines for treating MetS-CVD. Interestingly, six drugs are being tested to treat COVID-19, which unexpectedly offers a new potential host-targeting antiviral strategy. Conclusion: Collectively, we revealed the potential significance of the ATP5MG-centered network for developing drugs to treat MetS-CVD, which offers insights into the epigenetic regulation for metabolism-immunity highly integrated diseases.